Description of a new species of Dinidor Latreille (Hemiptera: Dinidoridae) from the Brazilian Amazon Rainforest, and new records of D. saucius Stål - López, Guilherme E. L.; Carrenho, Renan; Schwertner, Cristiano F. (Zootaxa, 2021)
Dinidor jograziae sp. nov., is described. The new species can be recognized by the relatively shorter mandibular plates which do not come in contact with each other anterior to the clypeus, by the dark brown hemelytral membranes, with darker, reticulate veins, and by having a relatively large portion of the connexiva exposed. We provide high-resolution photographs of important characters such as the head, pronotum, and the male and female external genitalia. We also provide new locality records for D. saucius from southern and southeastern Brazil, including the Atlantic Rain Forest region in the states of Rio de Janeiro, Santa Catarina and São Paulo.